Pemberian Pakan Tepung Maggot (Hermetia illucens) terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) - Mohammad Taufik Mu’min; Rully Tuiyo; Arafik Lamadi (Transbahasa, 2025)
Maggot is known to have a high content of protein and crude fat, which is 45-50% and 24-30%, respectively. This study aimed to determine the effect of maggot (Hermetia illucens) flour feed on the growth and survival of tilapia (Oreochromis niloticus) fish and to determine the best concentration of maggot (Hermetia illucens) flour feed on the growth and survival of tilapia (Oreochromis niloticus) fish. This research was conducted at the Fish Breeding Center of Gorontalo City from May to June 2024. This Study used an experimental method, consisting of 4 treatments and 3 repetitions. The treatment groups were P0 (0% maggot flour), P1 (25% maggot flour), P2 (50% maggot flour), and P3 (75% maggot flour). The data collection technique was obtained in 3 ways: calculation of absolute weight growth, absolute length escalation, and survival rate. The absolute increase in length and weight was analyzed by Analysis of Variance One Way using the F-test. Meanwhile, the survival of tilapia used a non-parametric test (Kruskall-Wallis test). Based on the analysis, it obtained that the average absolute length P3= 1.92 cm, P2= 1.51 cm, P1= 1.49 cm, and P0= 1.62 cm; average absolute weight P3= 1.43 gr, P2= 1.18 gr, P1= 1.14 gr, and P0= 1.25 gr; average of survival rate P3= 86.67%, P2= 80%, P1= 76.67%, and P0= 1.25%. In conclusion, the combination treatment of commercial feed and maggot (Hermetia illucens) flour did not have a significant effect on the length, weight, and survival rate of tilapia (Oreochromis niloticus) fish, with P>0.05.